PENGEMBANGAN E-COMIC SEBAGAI MEDIA PEMBELAJARAN SEJARAH UNTUK SISWA SMA PADA MATERI AGRESI MILITER BELANDA I DAN II - Arrahman, Ikhsan; Hastuti, Hera (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study aims to develop Indonesian history learning media on Dutch Military Aggression Materials I and II for class XI Senior Highschool. This study used research and development (R&D) methods, using the ADDIE development model. In this research only carried out until the stage of implementation (implementation). The analysis phase is carried out by conducting a needs and curriculum analysis. The design stage is carried out by making a summary of the material, creating a storyline, and drafting an e-comic design. The Development Stage is carried out by making images and text in e-comics using Adobe Photoshop software, at this stage validation is also carried out with material experts and media experts. Evaluation with material experts obtained an average of 3.70 included in the Very Eligible criteria, Assessment with media experts obtained an average of 3.88 included in the Very Eligible criteria. The implementation phase was carried out by testing the teacher and 32 students of class XI IPS 5 SMAN 3 Bukittinggi. The practicality assessment by the teacher gets an average of 3.83 with very practical criteria. From the practicality assessment by students, they get an average of 3.48 with very practical criteria. From the research data that has been done, it can be concluded that the e-comic media developed is feasible and practical for use in Indonesian history learning for class XI Senior Highschool.